2008
DOI: 10.1002/jnr.21640
|View full text |Cite
|
Sign up to set email alerts
|

Manganese potentiates nuclear factor‐κB‐dependent expression of nitric oxide synthase 2 in astrocytes by activating soluble guanylate cyclase and extracellular responsive kinase signaling pathways

Abstract: Inflammatory activation of glial cells is associated with neuronal injury in several degenerative movement disorders of the basal ganglia, including manganese neurotoxicity. Manganese (Mn) potentiates the effects of inflammatory cytokines on nuclear factor-κB (NF-κB)-dependent expression of nitric oxide synthase 2 (NOS2) in astrocytes, but the signaling mechanisms underlying this effect have remained elusive. It was postulated in the present studies that direct stimulation of cGMP synthesis and activation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 44 publications
6
59
0
Order By: Relevance
“…In the absence of microglia, Mn treatment alone was insufficient to increase expression of inflammatory genes in astrocytes, except for Nos2 , even at the highest dose examined (100 μM). These results may help to explain why previous studies in our laboratory and others that examined astrocyte inflammatory responses to Mn reported that cytokines, presumably from microglia, were required to activate astrocytes in the presence of low micromolar concentrations of Mn [7, 64]. The results of the present study also corroborate earlier findings that microglia were required for Mn-induced neuronal death in mixed glial-neuronal cultures [55].…”
Section: Discussionsupporting
confidence: 90%
“…In the absence of microglia, Mn treatment alone was insufficient to increase expression of inflammatory genes in astrocytes, except for Nos2 , even at the highest dose examined (100 μM). These results may help to explain why previous studies in our laboratory and others that examined astrocyte inflammatory responses to Mn reported that cytokines, presumably from microglia, were required to activate astrocytes in the presence of low micromolar concentrations of Mn [7, 64]. The results of the present study also corroborate earlier findings that microglia were required for Mn-induced neuronal death in mixed glial-neuronal cultures [55].…”
Section: Discussionsupporting
confidence: 90%
“…However, the direct involvement of ACHE and iNOS associated with cerebellum impairments has not been elucidated in manganese induced neurotoxicity. Recently, interesting evidences suggest that manganese neurotoxicity involves activation of microglia BV2 [11] and/or astrocytes [12] with an increase in nitric oxide (NO) production, leading to the damage of the adjacent neurons. These high levels of NO may make cerebellum more susceptible to oxidative and nitrosative stress and induces the formation of reactive nitrogen species (RNS) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have now built upon these initial findings, revealing that Mn can exacerbate LPS and cytokine-induced activation of both microglia and astrocytes, resulting in increased levels of TNFa, IL-1b, ROS, and NOS2 expression. [111][112][113][114][115] Increased levels of the aforementioned inflammatory genes has also been measured in both rodent 29,116 and non-human primate 117 studies with deletion or inhibition of these pathways showing neuroprotection. 18,116,118 To decipher the complex signaling mechanisms likely to influence development of a neuroinflammatory phenotype in Mn neurotoxicity, primary astrocytes and microglia can be isolated from neonatal mouse and the relative contributions of each cell type defined by using immunopurification-based methods to establish pure astroglial and microglial cultures from mixed isolates (Figure 12.1).…”
Section: Manganismmentioning
confidence: 97%